Principles of Economics - Greenlaw, Steven A.; Shapiro, David A.; MacDonald, Daniel (Open textbook library., 2023)
Principles of Economics 3e covers the scope and sequence of most introductory economics courses. The third edition takes a balanced approach to the theory and application of economics concepts. The text uses conversational language and ample illustrations to explore economic theories, and provides a wide array of examples using both fictional and real-world scenarios. The third edition has been carefully and thoroughly updated to reflect current data and understanding, as well as to provide a deeper background in diverse contributors and their impacts on economic thought and analysis. For example, the third edition highlights the research and views of a broader group of economists. Brief references and deeply explored socio-political examples have been updated to showcase the critical – and sometimes unnoticed – ties between economic developments and topics relevant to students. A fuller list of changes made in Principles of Economics 3e are described in the preface and the transition guide to help instructors transition to the third edition.